PIJAT BAYI EFEKTIF MENINGKATKAN KUALITAS TIDUR BAYI USIA 2-4 BULAN DI WILAYAH KERJA PUSKESMAS DELI TUA - Wigi Yuliana; Reisy Tane; Selamat Ginting (Jurnal Penelitian Keperawatan Medik, 2021)
Abstract Baby's growth and development can be optimized with good quality sleep, one way is baby massage. Researchers interviewed 15 mothers of infants. It was found that 15 mothers of babies never massaged their babies. This study aims to identify the effect of baby massage on the sleep quality of infants aged 3-12 months in the Deli Tua Public Health Center, Deli Serdang Regency.This type of research is a quasy experiment with a one group pretest-posttest design. The study population was infants aged 2-4 months. The sample of the study was 15 infants aged 2-4 months, using purposive sampling. The independent variable was infant massage and the dependent variable was the sleep quality of infants aged 2-4 months. The research instrument used a questionnaire. Wilcoxon statistical test data processing. The results showed that the sleep quality of infants aged 2-4 months before massage was mostly adequate, as many as 12 respondents (80.0%) and the quality of sleep for infants aged 2-4 months after massage was mostly good, as many as 14 respondents (93, 3%). Wilcoxon statistical test showed that the significant value of p-value = 0.000 <(0.05), so that H1 was accepted.The conclusion of this research is that there is an effect of infant massage on the sleep quality of babies aged 2-4 months in the working area of ​​the Deli Tua Health Center, Deli Serdang Regency.